2006
DOI: 10.1007/s00264-006-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Tibial plateau fractures treated with the less invasive stabilisation system

Abstract: Thirty-six tibial plateau fractures in 35 patients were treated with the less invasive stabilisation system (LISS). Patients' mean age was 42 years. There were 27 type C fractures and nine type B fractures according to AO/ OTA classification. The average time to healing was 4.2 months (3-7 months). Deep infection developed in two cases. One patient healed in 6°of varus, and seven patients had an increased articular angulation of 6°(4-8°) in the sagittal plane. There were no cases of loss of reduction, non-unio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 14 publications
(21 reference statements)
6
93
0
Order By: Relevance
“…Chaix et al [7] reported 86% good to excellent results by surgical means of treatment. Lee et al [8] reported good to excellent results by surgical means of less invasive stabilization system treatment. Feng et al [9] reported good results when fixed with LCP in comparison with dynamic compression plate (DCP) with an additional benefit of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Chaix et al [7] reported 86% good to excellent results by surgical means of treatment. Lee et al [8] reported good to excellent results by surgical means of less invasive stabilization system treatment. Feng et al [9] reported good results when fixed with LCP in comparison with dynamic compression plate (DCP) with an additional benefit of minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We had maximum number of 22 cases due to RTA (88%), followed by fall from height 3 cases (12%). Lee JA et al in a similar study reported an incidence of 80% due to RTA, 11.4% due to fall from height, 5.8% due to blow and 2.8% due to shotgun injury [6] . This suggests that distal femoral factures around knee joint commonly occurs due to high energy trauma.…”
Section: Discussionmentioning
confidence: 87%
“…Horesh Z et al in their study found an average age to be 40.6 year (range from 30 to 70 years) [5] . Lee JA et al in a similar study found the average age to be 42 years ranging from 18 to 82 years [6] . This reflects that distal femoral fractures around knee joint are common in young adult age group who are involved in outdoor activities.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations